Convolution Properties for Salagean-Type Analytic Functions Defined by q-Difference Operator - Çetinkaya, Asena (My University, 2019)
In this paper, we define Salagean-type analytic functions by using concept of q-derivative operator. We investigate convolution properties and coefficient estimates for Salagean-type analytic functions denoted by S-q(m,lambda) [A,B].
Keywords: Salagean Differential Operator; Q-difference Operator; Convolution; Coefficient Estimate